A new potential biomarker for dementia with Lewy bodies: Skin nerve α-synuclein deposits. (25th July 2017) - Donadio, Vincenzo; Incensi, Alex; Rizzo, Giovanni; Capellari, Sabina; Pantieri, Roberta; Stanzani Maserati, Michelangelo; Devigili, Grazia; Eleopra, Roberto; Defazio, Giovanni; Montini, Federico; Baruzzi, Agostino; Liguori, Rocco
Abstract : Objective: To investigate whether (1) phosphorylated α-synuclein (p-syn) deposits in skin nerves could be useful in differentiating dementia with Lewy bodies (DLB) from different forms of dementia and (2) small fiber neuropathy (SFN) is associated with DLB. Methods: We studied 18 well-characterized patients with DLB (11 with autonomic dysfunction), 23 patients with nonsynucleinopathy dementia (NSD; 13 with young-onset Alzheimer disease dementia, 6 frontotemporal dementia, and 4 vascular dementia), and 25 healthy controls. All participants underwent skin biopsies from proximal (i.e., cervical) and distal (i.e., thigh and distal leg) sites to study small nerve fibers and deposits of p-syn, considered the pathologic form of α-synuclein. Results: No p-syn was detected in any skin sample in patients with NSD and controls but was found in all patients with DLB. SFN was found in patients with DLB and the autonomic denervation of skin was more severe in patients with autonomic dysfunctions. Conclusions: (1) In autonomic skin nerves, p-syn is a sensitive biomarker for DLB diagnosis, helping to differentiate DLB from other forms of dementia, although this needs to be confirmed in a larger, more representative sample; and (2) skin autonomic neuropathy is part of the DLB pathology and may contribute to autonomic symptoms. Classification of evidence: This study provides Class III evidence that p-syn in skin nerve fibers on skin biopsy accurately distinguishes DLB from other forms of dementia.